Solución numérica de la ecuación de Laplace en una región plana acotada - Marín, Mariela; García Castañeda, Mauricio (MOMENTO, 1992)
Laplace's equation for a flat rectangular region is solved using a numerical routine based on the finite difference method. AIso, the graphic representation of the equipotential lines is presented by means of a Lagrange interpolation scheme.